Cytotoxicity and intracellular fate of PLGA and chitosan‐coated PLGA nanoparticles in Madin–Darby bovine kidney (MDBK) and human colorectal adenocarcinoma (Colo 205) cells. Issue 11 (11th June 2015) - Trif, Mihaela; Florian, Paula E.; Roseanu, Anca; Moisei, Magdalena; Craciunescu, Oana; Astete, Carlos E.; Sabliov, Cristina M.
Abstract Polymeric nanoparticles (NPs) are known to facilitate intracellular uptake of drugs to improve their efficacy, with minimum bioreactivity. The goal of this study was to assess cellular uptake and trafficking of PLGA NPs and chitosan (Chi)‐covered PLGA NPs in Madin–Darby bovine kidney (MDBK) and human colorectal adenocarcinoma (Colo 205) cells. Both PLGA and Chi–PLGA NPs were not cytotoxic to the studied cells at concentrations up to 2500 μg/mL. The positive charge conferred by the chitosan deposition on the PLGA NPs improved NPs uptake by MDBK cells. In this cell line, Chi–PLGA NPs colocalized partially with early endosomes compartment and showed a more consistent perinuclear localization than PLGA NPs. Kinetic uptake of PLGA NPs by Colo 205 was slower than that by MDBK cells, detected only at 24 h, exceeding that of Chi–PLGA NPs. This study offers new insights on NP interaction with target cells supporting the use of NPs as novel nutraceuticals/drug delivery systems in metabolic disorders or cancer therapy. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3599–3611, 2015.